Anti-microRNAs as Novel Therapeutic Agents in the Clinical Management of Alzheimer's Disease - Zhao, Yuhai; Alexandrov, Peter N.; Lukiw, Walter J. (Frontiers in Neuroscience, 2016)
Overview- One hundred and ten years since its first description Alzheimer's disease (AD) still retains its prominent status: (i) as the industrialized world's number one cause of age-related intellectual impairment and cognitive decline; (ii) as this country's most rapidly expanding socioeconomic and healthcare concern; and (iii) as an insidious, progressive and lethal neurological disorder of the human central nervous system (CNS) for which there is currently no adequate treatment or cure (Alzheimer, 1991; Alzheimer et al., 1991, 1995) [https://www.alz.org/facts/downloads/facts_figures_2015.pdf (2015)]. The concept of small non-coding RNAs (ncRNAs) as being involved in the etiopathogenesis of AD and age-related human neurodegenerative disease was first proposed about 25 years ago, however it was not until 2007 that specific microRNA (miRNA) abundance, speciation and localization to the hippocampal CA1 region (an anatomical area of the human CNS specifically targeted by the AD process) was shown to strongly associate with AD-type change when compared to age-matched controls (Lukiw et al., 1992; Lukiw, 2007; Schipper et al., 2007; Cogswell et al., 2008; Guerreiro et al., 2012). Currently about 400 reports address the potential link between disruptions in miRNA signaling and the development of various features associated with AD neuropathology (http://www.ncbi.nlm.nih.gov/pubmed/?term=micro+RNA+alzheimer's+disease). In this “Perspectives” paper we will highlight some of the most recent literature on anti-miRNA (AM; antagomir) therapeutic strategies and some very recent technological advances in the analysis and characterization of defective miRNA signaling pathways in AD compared to neurologically normal age-matched controls.